2017
DOI: 10.1080/13102818.2017.1334593
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nicotine on the adherence of Candida albicans ATCC 14053 and Candida parapsilosis ATCC 22019 and expression of selected binding-related genes

Abstract: Smoking is considered one of the main factors for development of dental plaque. Yeasts have been described to contribute to the plaque community. The aim of this study was to investigate the influence of nicotine on the growth of planktonic cells and biofilm, cell aggregation, surface hydrophobicity, cell adherence and binding-related genes expressed by Candida albicans and Candida parapsilosis in vitro. The relative number of viable fungal cells was determined based on viable plate counts. The biofilm growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
4
2
0
Order By: Relevance
“…In addition, nicotine from different sources enhanced hyphae formation in C. albicans biofilms (Figure 3). A similar study supported our data that N increased the biofilm formation of C. albicans [32]. In addition, a dose-response effect of CSC on promoting adhesion and biofilm formation of C. albicans as well as the inhibitory impact of CSC at higher concentrations was previously reported [3,22].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, nicotine from different sources enhanced hyphae formation in C. albicans biofilms (Figure 3). A similar study supported our data that N increased the biofilm formation of C. albicans [32]. In addition, a dose-response effect of CSC on promoting adhesion and biofilm formation of C. albicans as well as the inhibitory impact of CSC at higher concentrations was previously reported [3,22].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the inhibitory (MIC) and killing (MFC) effects of nicotine from different sources were determined and found to be within the range of nicotine levels present in the saliva of smokers [8,9]. Concentrations of N higher than 4 mg/mL showed an inhibitory effect on C. albicans (Table 1), which was in agreement with previous reports [8,32]. Interestingly, CSC and ECSC produced inhibitory effects against C. albicans at nicotine levels that were about an order of magnitude lower than for N (Table 1).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The possible mechanism of hydroxychavicol to inhibit the hyphal growth is by (1) altering the cellular morphology which lead to the unproductive cells and (2) delaying germination process by changing the expression of hyphae-related genes such RAS1, NRG1 and HWP1. Our finding strongly suggests that hydroxychavicol is effective against Candida species such C. albicans and this could support its usage in oral rinse to control and prevent candidal infection especially among target users like cigarette smokers [44] and immunocompromised patients [45].…”
Section: Transcriptional Response Of Ras1 Nrg1 and Hwp1 Gene To Hydrsupporting
confidence: 58%
“…Huang et al 45 found that nicotine stimulates S. gordonii planktonic cell growth, biofilm formation, aggregation, and gene expression translated into binding proteins. Furthermore, Shan et al 46 suggested that nicotine can enhance the growth of Candida albicans (C. albicans) and C. parapsilosisin vitro and influence their adherence to the surface of microplate wells that mimic the tooth surface adherence. These effects may promote later pathogen attachment to tooth surfaces, the accumulation of tooth calculus, and the development of periodontal disease in cigarette smokers.…”
Section: Resultsmentioning
confidence: 99%